Neuro-Sjögren: Peripheral Neuropathy With Limb Weakness in Sjögren's Syndrome - Seeliger, Tabea; Prenzler, Nils K.; Gingele, Stefan; Seeliger, Benjamin; Körner, Sonja; Thiele, Thea; Bönig, Lena; Sühs, Kurt-Wolfram; Witte, Torsten; Stangel, Martin; Skripuletz, Thomas (Frontiers in Immunology, 2019)
Objective: Sjögren’s syndrome is a heterogeneous inflammatory disorder frequently involving peripheral nerves with a wide spectrum of sensory modalities and distribution patterns. The objective of this cross-sectional study was to determine characteristics of Sjögren’s syndrome as a cause for severe neuropathy with limb weakness. Methods: 184 patients with polyneuropathy associated with limb weakness underwent routine diagnostics including investigations for Sjögren’s syndrome. 44 patients with Sjögren’s syndrome (ACR-EULAR classification criteria) and severe neuropathy were identified. Results: Sjögren’s syndrome was found at a median age of 63 years and the gender distribution showed a balanced female-male ratio of 1:1. Anti-SSA(Ro) antibodies were detected in 48% while seronegative patients were diagnosed with Sjögren’s syndrome based on sialadenitis on minor salivary gland biopsy with a focus score ≥1. The majority of patients (93%) were diagnosed with Sjögren’s syndrome after neurological symptoms appeared. Limbs were symmetrically involved in 84% of patients (57% tetraparesis, 27% paraparesis). Sensory function was not affected in 11% of patients indicating that Sjögren’s syndrome associated neuropathy can present as a pure motor syndrome. Electrophysiological measurements did not reveal pathognomonic findings (23% demyelinating pattern, 36% axonal pattern, 41% both demyelinating and axonal damage signs). More than half of our patients fulfilled the EFNS diagnostic criteria for CIDP indicating that distinction between Neuro-Sjögren and other causes of neuropathy such as CIDP is challenging. Interpretation: Our findings show that severe neuropathy with limb weakness is often associated with Sjögren’s syndrome. This is of great importance in identifying and understanding the causes of immune mediated polyneuropathy.